Developing Critical Reading Skills Teaching Materials with A Moral Message Based on The Short Story by Helby Tiana Rosa to The Class - Jamilah, Jamilah; Sutikno, Sutikno (PT Inovasi Pratama Internasional, 2024)
The use of short story teaching materials has great potential in students' reading skills. The purpose of this study is to determine the development and validation of teaching materials sourced from Helvy Tiada Rosa's short story for grade XI students of SMA Negeri 1 Galang Deli Serdang Regency for the 2023-2024 Learning Year. This research method uses the development of the R&D cycle of Borg and Gall. The steps in this study are data collection, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and mass results. His research instruments are non-tests and tests. Research uses material experts to validate teaching materials. Data analysis techniques with descriptive analysis. The results of the development of critical reading skills teaching materials containing moral messages sourced from Helvy Tiada Rosa's short story for grade XI of SMA Negeri 1 Galang are included in the